FEAR OF MISSING OUT (FOMO) AND ITS IMPACT ON THE MENTAL HEALTH OF SOCIAL MEDIA USERS ACROSS GENERATIONS - Ratu, Sri Caitanya Maha; Tobing, David Hizkia (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of Fear of Missing Out (FoMO) has increasingly emerged as a pressing psychological issue among social media users of all ages, particularly across Generation X, Millennials (Generation Y), and Generation Z. This study seeks to thoroughly examine the evolution of FoMO and its far-reaching implications for mental health, particularly anxiety and social connectedness. Employing a comprehensive literature review methodology, this research synthesizes findings from ten scholarly sources published between 2014 and 2024. The results consistently reveal a significant correlation between the frequency and intensity of social media engagement and elevated experiences of FoMO, which are often accompanied by emotional distress and behavioral concerns. Generation X often encounters FoMO through technological unfamiliarity and social comparison, leading to feelings of exclusion and unease. Millennials tend to experience heightened psychological pressure to remain perpetually connected, contributing to compulsive online behavior and greater vulnerability to stress. Although Generation Z is typically well-versed in digital environments, their constant desire to remain updated with peer activities and social trends renders them equally susceptible to the psychological effects of FoMO. This paper aims to contribute to the growing discourse on digital wellness by offering insights into the generational nuances of FoMO and its broader consequences for emotional resilience and mental well-being.